The Correlation between EFL Students’ Attitudes towards Their Writing Ability: (A Case Study at First Grade of One Senior High School in Bandung) - Astri Dwi Floranti; Hanif Nurcholish Adiantika (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2021)
This study aims at examining the relationship between students’ attitude towards their writing ability. This study employed quantitative study by using Pearson-product correlation. The samples were randomly selected 35 students out of the total population 70 students in one senior high school in Bandung. The Data were obtained through questionnaire with regard to attitude and writing proficiency which are appropriate with several criteria of each writing element to scrutinize the correlation between students’ attitude and writing skill ability. The findings indicate that attitude has moderate correlation (.456) with students’ writing ability. In other words, it is obvious that attitudes are very essential for students to increase their writing ability. The English teachers are suggested to figure out the prominence of attitudes to their students for it has been found that attitudes is able to significantly contribute to the students’ writing ability.